Fresh and Hardened Properties of Brick Aggregate Concrete with Maximum Aggregate Sizes of 10 mm to 75 mm - Tarek Uddin Mohammed; Aziz Hasan Mahmood; Adnan Sakib; Fahim Ahmed Khan; Shafakat Islam Sopnil (Construction Materials, 2023)
The fresh and mechanical properties of concrete made with brick aggregates of eight different maximum aggregate sizes (MAS), i.e., 10 mm, 12.5 mm, 19 mm, 25 mm, 37.5 mm, 50 mm, 63 mm, and 75 mm, were investigated. The other parameters studied were sand-to-aggregate volume ratio (s/a) (0.40 and 0.45), W/C (0.45, 0.50, and 0.55), and cement content (375 kg/m3 and 400 kg/m3). In total, 80 different concrete mixes were studied; the perimeter of the interfacial transition zone (ITZ) along the brick aggregates was quantified with an image-analysis software and the microstructure along the ITZ was investigated using a scanning-electron microscope (SEM) to corroborate the hardened properties of the concrete. Although larger MAS leads to greater slump in concrete, its effect on hardened properties is linked to other design parameters. For a cement content of 375 kg/m3 and W/C of 0.45 and 0.50, the compressive strength of concrete increases (by up to 5%–15%) with increases in MAS of up to 37.5 mm irrespective of s/a (0.40 and 0.45) and then reduces gradually. For all other cases, the compressive strength of concrete is reduced with increases in MAS. The SEM imaging confirmed the presence of weak and porous ITZ and the deposition of ettringite in the voids left by entrapped bleed water under large aggregates. The compressive strength also increased with increases in s/a from 0.40 to 0.45, predominantly for smaller MAS. Correlations between mechanical properties of concrete and stress–strain curves are proposed for different MAS.